Intestinal microflora shaping factors: emphasis on lipids - S. V. Belmer (Лечащий Врач)
The totality of microorganisms closely interacting with each other and with human cells is currently considered as another organ in the human body and is called the «microbiota». The functions of the intestinal microbiota are very diverse: anti-infective protection, modulation of the inflammatory and immune response, synthesis of compounds necessary for the body (for example, vitamins, shortchain fatty acids), participation in the digestion of a number of nutrients, as well as the regulation of intestinal motility, proliferation and differentiation of intestinal epithelial cells. It is the intestine that is the most densely populated biotope of the human body, and the population of microorganisms of the gastrointestinal tract is the most diverse and numerous. The settlement of the gastrointestinal tract begins in utero and enters the active phase after birth. Further progressive colonization of the child's digestive tract in the first months of life is provided by the mother's vaginal microflora during natural childbirth, breastfeeding, contact with the environment, as well as the consistent introduction of a variety of foods into the diet. In the study of L. Wang et al. (2021) analyzed the growth of several species of bacteria that dominate the intestines of infants by culturing on calcium palmitate media. This study was carried out by the Department of Medical Microbiology of the University of Groningen (Netherlands), the Medical Clinic of the University of Groningen and a goat milk formula company. Of all the tested bacteria, the growth of bifidobacteria and F. prausnitzii decreased when calcium palmitate was introduced into the medium, and the growth of Bifidobacterium infantis was completely stopped. Calcium palmitate reduced the thickness of the F.prausnitzii cell membrane, disrupted the fatty acid composition of the cell membrane and the function of membrane proteins involved in ion transport. The findings indicate that modification of the fat of formula-feeding formulas by the administrationof β-palmitate may promote the development of the gut microbiota in formula-fed infants by supporting the colonization of important beneficial bacteria at an early age.